ANALISIS MODEL SISTEM MANAJEMEN PEMBELAJARAN (Studi Kasus Desain Program Literasi Numerasi Terpadu di SD Negeri Pondok Pinang 08, Jakarta Selatan) - Adi Sanusi; Fahmi Hauzan Rafif; Nasuhi; Gofur Ahmad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the implementation of a Learning Management System Model (MSP) through a two-layer approach—the ADDIE model as a macro framework at the program level and the ASSURE model as a micro framework at the classroom level—at SD Negeri Pondok Pinang 08, South Jakarta. The school, designated as a school reformer (sekolah penggerak), faced significant challenges in improving literacy and numeracy competencies among Grade IV–V students, with approximately 41% classified as below competent in reading literacy and 44% in numeracy based on the 2024/2025 National Assessment and internal diagnostic results. A descriptive-analytic case study method was employed, drawing on assessment data, classroom observations, teacher interviews, and program documentation. Results indicate that consistent implementation of the ADDIE– ASSURE model reduced the percentage of below-competent students by 12–16 percentage points after one semester, increased student active engagement, and improved the quality of instructional materials developed by teachers. The main implementation barriers identified were inconsistent formative evaluation documentation and uneven teacher capacity in systematic instructional design. Strategic recommendations include strengthening professional learning communities, systematizing formative documentation, and conducting module pilot testing prior to full implementation. This study contributes to the development of a contextual learning management model for urban elementary schools that can be widely replicated.